Digital tools for enriching informal inquiry-based mobile learning: The design of the TraceReaders location-based augmented reality learning platform - Kyza, Eleni A.; Georgiou, Ioannis (My University, 2016)
There is widespread discussion around the world about the purpose and usefulness of the current schooling structures. While it is well understood that learning can happen anywhere and everywhere most educational practices in K-12 are confined within the walls of a classroom and the school. This oxymoron challenges our understanding of how people learn, as it narrowly defines learning and excludes the opportunities that an expanded and digitally mediated definition of learning can offer. Cutting edge technologies that enable the digital augmentation of the real world can provide enriched learning experiences, through situating the learning content in authentic contexts and promoting inquiry-based learning. These ideas are reflected in the design of the TraceReaders mobile augmented reality learning platform. This contribution describes the TraceReaders platform for supporting students' reflective inquiry in situ. TraceReaders was iteratively developed and empirically validated using a designbased methodology. We present two case studies of inquiry learning, one from science education and one from history education, used with 11th grade and 3rd grade students and discuss the affordances and challenges of such a tool. We conclude our discussion with lessons learned from empirical studies about the design and effectiveness of the TraceReaders platform and discuss future steps.
Keywords: Augmented reality technologies; Informal learning; Inquiry; Mobile learning